High-hardness anti-reflection film glass and preparation method thereof
Through the proportional mixing and plating technology of acidic and alkaline sols, combined with calcination and heat treatment, the balance of hardness and light transmittance of the urgent film glass is solved, and an urgent film glass with high hardness and high light transmittance is achieved.
Patent Information
- Application Number
- CN202410919116.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-10
AI Technical Summary
The existing amphipathic film glass has low hardness and is prone to damage. The light transmittance will decrease when the hardness is increased, making it difficult to balance the performance of both.
By mixing the acid sol with the alkaline sol in a specific proportion, an impermeable plating solution is formed and plating on the glass surface, combining calcination and heat treatment, the plating structure is optimized to improve hardness and light transmittance.
The balance between high hardness and high light transmittance is achieved, the surface defects of the coating are reduced, and the comprehensive performance of the urinary film glass is improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-reflection glass, in particular to a high-hardness anti-reflection film glass and a preparation method thereof. Background Art
[0002] With the continuous development of science and technology, the use of clean energy to reduce energy loss has been widely studied. Among them, photovoltaic power generation is a process of converting solar energy into electrical energy. It is an important component of clean energy and is of great significance to reducing greenhouse gas emissions and reducing dependence on fossil fuels.
[0003] With the deepening of photovoltaic power generation research, anti-reflection film glass has received widespread attention as one of the important components of photovoltaic power generation. Anti-reflection film glass is generally composed of a glass substrate and a coating on its surface that can increase the light transmittance. In the prior art, the anti-reflection film is coated on the surface of glass, including physical and chemical methods; compared with other methods, the sol-gel method is simpler and has lower costs, and is one of the most promising methods. However, the hardness of the anti-reflection film glass is not high at present, and it is easy to be scratched or damaged, thus affecting the use effect; or when the hardness is high, the overall light transmittance will decrease, and it is difficult to balance the two properties of high hardness and high light transmittance.
[0004] In summary, solving the above problems and preparing a high-hardness anti-reflection film glass with excellent performance is of great value. Summary of the invention
[0005] The object of the present invention is to provide a high-hardness anti-reflection film glass and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A method for preparing high-hardness anti-reflection film glass comprises the following steps:
[0008] Step 1: Add tetraethyl orthosilicate, silane coupling agent and deionized water to anhydrous ethanol in sequence and stir evenly; add hydrochloric acid dropwise and stir for 3±0.5 hours; age at 30-35° C. for 2-3 days to obtain an acidic sol;
[0009] Tetraethyl orthosilicate and deionized water are sequentially added to anhydrous ethanol and stirred evenly; ionic liquid and ammonia water are sequentially added and stirred for 3±0.5 hours; aging is performed at 30-35°C for 3-5 days, and condensing and refluxing at 75-80°C for 8-12 hours to obtain an alkaline sol;
[0010] Step 2: Evenly mix the alkaline sol and the acidic sol in proportion to obtain an anti-reflection plating solution;
[0011] Step 3: pretreat the glass substrate, and then coat the anti-reflection coating solution on its surface; dry at 75-80°C for 1-2 hours; calcine at 400-420°C for 1-2 hours in an air atmosphere; wash and blow dry with nitrogen; heat treat at 150-200°C for 20-30 minutes in a nitrogen atmosphere to obtain high-hardness anti-reflection coated glass.
[0012] In the scheme, an acidic sol and an alkaline sol are mixed to form an anti-reflection plating solution for plating, which effectively optimizes and complements the advantages and disadvantages of the two sols. Generally speaking, if only an acidic sol is used, the hardness is high, but the maximum transmittance is low; if only an alkaline sol is used, although the maximum transmittance is high, the overall hardness is low; therefore, the two are mixed in the scheme to obtain an anti-reflection plating solution; in the coating, the acid catalysis obtains a mesh silicon, which connects the base-catalyzed silicon dioxide to form a uniform anti-reflection network, thereby balancing the hardness and transmittance of the anti-reflection coated glass.
[0013] In addition, the scheme carried out cleaning and post-treatment after calcination, the purpose of which was to reduce the residue of the inner membrane plate agent and improve the transmittance. The washing process was: first in a detergent (including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest was deionized water), cleaned under 500W ultrasonic waves for 5 to 10 minutes, and then rinsed with deionized water.
[0014] More optimally, in the anti-reflection plating solution, the volume ratio of alkaline sol to acidic sol is 5 to 5.5:1. In the scheme, the ratio of the two sols is limited, and this ratio can optimize the balance between transmittance and hardness to maximize the overall performance. Among them, if the ratio is not appropriate, it will have a negative impact; for example, when there is too much acidic sol, the condensation increases, resulting in the agglomeration of silica particles in the sol, forming local precipitation, which makes the coating surface defective and affects the overall performance.
[0015] Preferably, the acidic sol comprises the following raw materials: by weight, 10 parts of tetraethyl orthosilicate, 16-17 parts of anhydrous ethanol, 1.5-2 parts of silane coupling agent, 2.5-3.5 parts of deionized water, and 0.29-0.31 parts of hydrochloric acid;
[0016] The alkaline sol comprises the following raw materials: by weight, 10 parts of tetraethyl orthosilicate, 64-65 parts of anhydrous ethanol, 1.5-2.5 parts of deionized water, 1.2-1.6 parts of ionic liquid, and 3-3.5 parts of ammonia water.
[0017] In the scheme, silane coupling agent is further introduced into the acidic sol, and ionic liquid is introduced into the alkaline sol; firstly, the aging stability in the acidic sol and alkaline sol processes is improved, and secondly, the stability of the mixing process is increased, thereby improving the orderliness of the voids after the anti-reflection plating solution forms a coating, thereby ensuring excellent light transmittance under high hardness.
[0018] More optimally, the method of coating the anti-reflection plating solution is an immersion pulling method, and the pulling speed is 400-500 μm / s. In the scheme, the pulling speed is limited, and under the precursor of the anti-reflection plating solution in the scheme, the pulling speed has a more optimized coating performance.
[0019] More optimally, the preparation method of the silane coupling agent is: adding silane coupling agent A1387 to toluene, adding epoxy polyethylene glycol monomethyl ether, reacting at 60-80°C for 6-8 hours, and removing toluene by reduced pressure distillation to obtain the silane coupling agent; wherein the mass ratio of silane coupling agent A1387 to epoxy polyethylene glycol monomethyl ether is 1:2-4.
[0020] In the scheme, based on the macromolecular silane coupling agent A1387, polyethylene glycol monomethyl ether is grafted by the reaction of amino and epoxy groups; and it is used as an inner membrane plate to be uniformly dispersed in the acid sol, effectively inhibiting the agglomeration of nano-silica during the mixing process. At the same time, the introduction of this substance improves the orderliness of the particle dispersion in the coating after heat treatment, thereby improving the transmittance. At the same time, because it can improve the intermolecular force, interparticle force, and the interface force between the coating and the glass matrix through hydrogen bonding, its introduction also improves the hardness. It should be noted that the amount of its introduction should not be too much, as too much will lead to a decrease in transmittance; at the same time, the molecular weight of polyethylene glycol monomethyl ether in epoxy polyethylene glycol monomethyl ether needs to be limited, which will also affect the transmittance.
[0021] More optimally, the preparation method of the epoxy polyethylene glycol monomethyl ether is: polyethylene glycol monomethyl ether and tetra-n-butylammonium chloride are evenly mixed, and epichlorohydrin is added at 35-40° C.; the temperature is increased to 50-55° C., a sodium hydroxide solution is added, stirred for 6-8 hours, and post-treated to obtain epoxy polyethylene glycol monomethyl ether; wherein the molar ratio of polyethylene glycol monomethyl ether to epichlorohydrin is 1:1-1.1.
[0022] More optimally, the average molecular weight of the polyethylene glycol monomethyl ether is between 380 and 550.
[0023] More optimally, the preparation method of the ionic liquid is as follows: (1) dissolving elemental sodium in anhydrous ethanol at room temperature under a nitrogen atmosphere to obtain sodium ethoxide; adding imidazole at room temperature, stirring at 55-60°C for 2-3 hours to obtain sodium imidazole; adding 2-chloroethyl vinyl ether, reflux at 78-80°C for 24 hours; post-treating to obtain monovinyl ether imidazole; (2) adding monovinyl ether imidazole to anhydrous ethanol, adding 2-chloroethyl vinyl ether, reflux at 78-80°C for 24 hours, cooling to room temperature, adding AIBN (azobisisobutyronitrile) and silane coupling agent A172, reacting at 70-75°C for 6-8 hours, post-treating to obtain an ionic liquid.
[0024] In the scheme, in order to improve the stability of the alkaline sol after adding the acidic sol, an ionic liquid was prepared and added to the alkaline sol, which improved the stability of the nano-silica in the alkaline sol, inhibited agglomeration, inhibited the generation of local large particles, and improved the stability of the anti-reflection plating solution, thereby improving the transmittance.
[0025] More optimally, the raw materials of the monovinyl ether imidazole include the following components: by weight, 0.2-0.25 parts of elemental sodium, 20-22 parts of anhydrous ethanol, 0.7-0.72 parts of imidazole, and 2.1-2.3 parts of 2-chloroethyl vinyl ether; the raw materials of the ionic liquid include the following components: by weight, 3-3.2 parts of monovinyl ether imidazole, 10-12 parts of anhydrous ethanol, 1.05-1.07 parts of 2-chloroethyl vinyl ether, 0.01-0.02 parts of AIBN, and 4.4-4.5 parts of silane coupling agent A172.
[0026] More optimally, a method for preparing high-hardness anti-reflection film glass produces high-hardness anti-reflection film glass.
[0027] Compared with the prior art, the beneficial effects of the present application are as follows: (1) an anti-reflection coating solution is obtained by mixing an acidic sol and an alkaline sol in a specific ratio, and the synergistic optimization and complementation are effectively balanced to obtain a high-hardness anti-reflection film glass with excellent transmittance; (2) a macromolecular silane coupling agent containing a polyethylene glycol segment is prepared and added to the acidic sol, and an ionic liquid is prepared and added to the alkaline sol. On the basis of improving the stability of the two sols, the stability of the anti-reflection coating solution during the mixing process is improved, thereby reducing the surface defects of the anti-reflection coating solution after plating and increasing the transmittance of the high-hardness anti-reflection film glass. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] It should be noted that there are no special restrictions on the purchase manufacturers of all raw materials involved in the present invention, which are exemplified as follows: in the following embodiments, the concentration of hydrochloric acid is 3638%; the concentration of ammonia water is 2528%; the purity of tetraethyl orthosilicate is 99%; and the light transmittance of the glass substrate is 80%.
[0030] Preparation of silane coupling agent: (1) Polyethylene glycol 400 monomethyl ether and tetra-n-butylammonium chloride are uniformly mixed, and epichlorohydrin is added at 40° C., wherein the molar ratio of polyethylene glycol monomethyl ether to epichlorohydrin is 1:1.05; the temperature is raised to 55° C., sodium hydroxide solution is added, stirred for 6 hours, and post-treated to obtain epoxy polyethylene glycol monomethyl ether; (2) silane coupling agent A1387 is added to toluene, and epoxy polyethylene glycol monomethyl ether is added, wherein the mass ratio of silane coupling agent A1387 to epoxy polyethylene glycol monomethyl ether is 1:3.5; the mixture is reacted at 80° C. for 6 hours, and toluene is removed by reduced pressure distillation to obtain a silane coupling agent.
[0031] Preparation of ionic liquid: (1) Under nitrogen atmosphere, 0.23 parts of elemental sodium are dissolved in 20 parts of anhydrous ethanol at room temperature to obtain sodium ethoxide; 0.72 parts of imidazole are added at room temperature, and stirred at 55°C for 2 hours to obtain sodium imidazole; 2.15 parts of 2-chloroethyl vinyl ether are added, and refluxed at 7880°C for 24 hours; post-treatment is performed to obtain monovinyl ether imidazole; (2) 3 parts of monovinyl ether imidazole are added to 12 parts of anhydrous ethanol, 1.06 parts of 2-chloroethyl vinyl ether are added, refluxed at 80°C for 24 hours, cooled to room temperature, 0.01 parts of AIBN and 4.4 parts of silane coupling agent A172 are added, and the reaction is carried out at 75°C for 6 hours, and post-treatment is performed to obtain an ionic liquid.
[0032] Embodiment 1: A method for preparing high-hardness anti-reflection film glass, comprising the following steps:
[0033] Step 1: (1) 10 parts of tetraethyl orthosilicate, 1.8 parts of silane coupling agent, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; and the mixture is aged at 30° C. for 3 days to obtain an acidic sol;
[0034] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.5 parts of ionic liquid and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0035] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 5.2:1 to obtain an anti-reflection plating solution;
[0036] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0037] Embodiment 2: A method for preparing high-hardness anti-reflection film glass, comprising the following steps:
[0038] Step 1: (1) 10 parts of tetraethyl orthosilicate, 1.5 parts of silane coupling agent, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; and the mixture is aged at 30° C. for 3 days to obtain an acidic sol;
[0039] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.2 parts of ionic liquid and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0040] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 5:1 to obtain an anti-reflection plating solution;
[0041] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0042] Embodiment 3: A method for preparing high-hardness anti-reflection film glass, comprising the following steps:
[0043] Step 1: (1) 10 parts of tetraethyl orthosilicate, 2 parts of silane coupling agent, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; and the mixture is aged at 30° C. for 3 days to obtain an acidic sol;
[0044] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.6 parts of ionic liquid and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0045] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 5.5:1 to obtain an anti-reflection plating solution;
[0046] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0047] Comparative Example 1: Based on Example 1, the silane coupling agent used in Example 1 is replaced by silane coupling agent A1170 and; the details are as follows:
[0048] Step 1: (1) 10 parts of tetraethyl orthosilicate, 1.2 parts of silane coupling agent A1170, 0.6 parts of polyethylene glycol 400 monomethyl ether, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; aged at 30° C. for 3 days to obtain an acidic sol;
[0049] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.5 parts of ionic liquid and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0050] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 5.2:1 to obtain an anti-reflection plating solution;
[0051] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0052] Comparative Example 2: Based on Example 1, the ionic liquid used in Example 1 is replaced with 1-ethyl-3-methylimidazolium chloride; the details are as follows:
[0053] Step 1: (1) 10 parts of tetraethyl orthosilicate, 1.8 parts of silane coupling agent, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; and the mixture is aged at 30° C. for 3 days to obtain an acidic sol;
[0054] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.5 parts of 1-ethyl-3-methylimidazolium chloride and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0055] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 5.2:1 to obtain an anti-reflection plating solution;
[0056] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0057] Comparative Example 3: Based on Example 1, the proportion of the acidic sol was increased, as follows:
[0058] Step 1: (1) 10 parts of tetraethyl orthosilicate, 1.8 parts of silane coupling agent, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; and the mixture is aged at 30° C. for 3 days to obtain an acidic sol;
[0059] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.5 parts of ionic liquid and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0060] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 3:1 to obtain an anti-reflection plating solution;
[0061] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0062] Comparative Example 4: Based on Example 1, the proportion of the acidic sol is reduced, as follows:
[0063] Step 1: (1) 10 parts of tetraethyl orthosilicate, 1.8 parts of silane coupling agent, and 2.8 parts of deionized water are added to 16.2 parts of anhydrous ethanol in sequence and stirred evenly; 0.3 parts of hydrochloric acid is added dropwise and stirred for 3 hours; and the mixture is aged at 30° C. for 3 days to obtain an acidic sol;
[0064] (2) 10 parts of tetraethyl orthosilicate and 1.8 parts of deionized water were added to 64.5 parts of anhydrous ethanol in sequence and stirred evenly; 1.5 parts of ionic liquid and 3.2 parts of ammonia water were added in sequence and stirred for 3 hours; aged at 30° C. for 5 days, and condensed and refluxed at 80° C. for 12 hours to obtain an alkaline sol;
[0065] Step 2: Evenly mix the alkaline sol and the acidic sol in a volume ratio of 7:1 to obtain an anti-reflection plating solution;
[0066] Step 3: Pretreat the glass substrate (the pretreatment is to use 15wt% dilute hydrochloric acid to clean for 15 minutes, ethanol to clean for 15 minutes, and deionized water to rinse in sequence), and then apply the anti-reflection coating solution on its surface by immersion pulling method, and the pulling speed is 500μm / s; dry at 80℃ for 1 hour; calcine at 400℃ in air atmosphere for 1 hour; clean in a detergent including 1% glycolic acid, 2wt% citric acid, 0.1wt% TritonX-100, and the rest is deionized water under 500W ultrasonic wave for 6 minutes, then rinse with deionized water and blow dry with nitrogen; heat treat at 150℃ for 30 minutes in nitrogen atmosphere to obtain high hardness anti-reflection coated glass.
[0067] Performance test: The high-hardness anti-reflection coated glass prepared in the embodiment and the comparative example was tested for maximum light transmittance using a spectrophotometer; the surface hardness of the high-hardness anti-reflection coated glass was tested using a pencil hardness tester; the obtained data are shown in the following table:
[0068] sample Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Maximum light transmittance% 92.8 92.1 91.2 87.8 85.7 88.9 90.1 Surface hardness H 8 8 8 6 7 8 6
[0069] Conclusion: From the data in the above table, we can see that in the scheme, by introducing a macromolecular silane coupling agent containing polyethylene glycol segments into the acidic sol and introducing a specially prepared ionic liquid into the alkaline sol, and mixing them in a specific ratio to achieve a synergistic balance of performance, an anti-reflection film glass with high light transmittance and high hardness is obtained. From the comparative data, we can see that the replacement of the silane coupling agent, the replacement of the ionic liquid, and the adjustment of the ratio will affect the uniformity and stability of the anti-reflection coating solution, thereby causing surface defects in the coating and affecting the performance of the anti-reflection film glass.
[0070] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing high-hardness anti-reflection film glass, characterized in that: The following steps are involved: Step 1: Add tetraethyl orthosilicate, silane coupling agent and deionized water to anhydrous ethanol in sequence and stir evenly; add hydrochloric acid dropwise and stir for 3±0.5 hours; age at 30-35° C. for 2-3 days to obtain an acidic sol; Tetraethyl orthosilicate and deionized water are sequentially added to anhydrous ethanol and stirred evenly; ionic liquid and ammonia water are sequentially added and stirred for 3±0.5 hours; aging is performed at 30-35°C for 3-5 days, and condensing and refluxing at 75-80°C for 8-12 hours to obtain an alkaline sol; Step 2: Evenly mix the alkaline sol and the acidic sol in proportion to obtain an anti-reflection plating solution; Step 3: pre-treat the glass substrate, and then coat the anti-reflection coating solution on the surface thereof; dry at 75-80° C. for 1-2 hours; and calcine at 400-420° C. for 1-2 hours in an air atmosphere; Washing, nitrogen drying; Heat treatment is performed at 150-200° C. for 20-30 minutes in a nitrogen atmosphere to obtain a high-hardness anti-reflection coated glass; In the antireflection plating solution, the volume ratio of alkaline sol to acidic sol is 5 to 5.5:1; The preparation method of the silane coupling agent is as follows: adding silane coupling agent A1387 to toluene, adding epoxy polyethylene glycol monomethyl ether, reacting at 60-80° C. for 6-8 hours, and removing toluene by reduced pressure distillation to obtain the silane coupling agent; wherein the mass ratio of silane coupling agent A1387 to epoxy polyethylene glycol monomethyl ether is 1:2-4; The preparation method of the ionic liquid is as follows: (1) dissolving elemental sodium in anhydrous ethanol at room temperature under a nitrogen atmosphere to obtain sodium ethoxide; adding imidazole at room temperature, stirring at 55-60° C. for 2-3 hours to obtain sodium imidazole; adding 2-chloroethyl vinyl ether, refluxing at 78-80° C. for 24 hours; post-treating to obtain monovinyl ether imidazole; (2) adding monovinyl ether imidazole to anhydrous ethanol, adding 2-chloroethyl vinyl ether, refluxing at 78-80° C. for 24 hours, cooling to room temperature, adding AIBN and silane coupling agent A172, reacting at 70-75° C. for 6-8 hours, post-treating to obtain an ionic liquid.
2. The method for preparing a high-hardness anti-reflection film glass according to claim 1, characterized in that: The acidic sol includes the following raw materials: by weight, 10 parts of tetraethyl orthosilicate, 16-17 parts of anhydrous ethanol, 1.5-2 parts of silane coupling agent, 2.5-3.5 parts of deionized water, and 0.29-0.31 parts of hydrochloric acid; The alkaline sol comprises the following raw materials: by weight, 10 parts of tetraethyl orthosilicate, 64-65 parts of anhydrous ethanol, 1.5-2.5 parts of deionized water, 1.2-1.6 parts of ionic liquid, and 3-3.5 parts of ammonia water.
3. The method for preparing a high-hardness anti-reflection film glass according to claim 1, characterized in that: The method for coating the anti-reflection plating solution is an immersion pulling method, and the pulling speed is 400 to 500 μm / s.
4. The method for preparing a high-hardness anti-reflection film glass according to claim 1, characterized in that: The preparation method of the epoxy polyethylene glycol monomethyl ether comprises: uniformly mixing polyethylene glycol monomethyl ether and tetra-n-butylammonium chloride, adding epichlorohydrin at 35-40° C.; heating to 50-55° C., adding sodium hydroxide solution, stirring for 6-8 hours, and post-treating to obtain the epoxy polyethylene glycol monomethyl ether; wherein the molar ratio of polyethylene glycol monomethyl ether to epichlorohydrin is 1:1-1.
1.
5. The method for preparing a high-hardness anti-reflection film glass according to claim 4, characterized in that: The average molecular weight of the polyethylene glycol monomethyl ether is between 380 and 550.
6. The method for preparing a high-hardness anti-reflection film glass according to claim 1, characterized in that: The raw materials of the monovinyl ether imidazole include the following components: by weight, 0.2-0.25 parts of elemental sodium, 20-22 parts of anhydrous ethanol, 0.7-0.72 parts of imidazole, and 2.1-2.3 parts of 2-chloroethyl vinyl ether; the raw materials of the ionic liquid include the following components: by weight, 3-3.2 parts of monovinyl ether imidazole, 10-12 parts of anhydrous ethanol, 1.05-1.07 parts of 2-chloroethyl vinyl ether, 0.01-0.02 parts of AIBN, and 4.4-4.5 parts of silane coupling agent A172. 7 . The high-hardness anti-reflection film glass prepared according to the method for preparing high-hardness anti-reflection film glass according to any one of claims 1 to 6 .
Citation Information
Patent Citations
Photovoltaic glass and preparation method thereof
CN112723755A
Powdery silica composite particles, process of producing same, silica composite particle dispersion, and resin composition
US20090047518A1